School Health Business Management - Ningsih, Yurni; Fitria, Happy; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2022)
The goal of this study was to investigate the school health business management in State Primary School 157 Palembang. This study was carried out in qualitative and interview was used as instrument. The results showed that the health business management has been going well because in its implementation it has involved all parties, from the school principal, teachers, students, staff, school committee, health center staff and the surrounding community. It contributes to others school to apply health business management as what was done in State Primary School 157 Palembang.